Sex-Based Disparities Among Cancer Clinical Trial Participants. (27th July 2019) - Ludmir, Ethan B; Fuller, C David; Moningi, Shalini; Mainwaring, Walker; Lin, Timothy A; Miller, Austin B; Jethanandani, Amit; Espinoza, Andres F; Verma, Vivek; Smith, Benjamin D; Smith, Grace L; VanderWalde, Noam A; et al.
Abstract: Landmark investigation two decades ago demonstrated sex-based disparities among participants in cancer cooperative group trials. Although federal efforts have aimed to improve representation of female patients in government-sponsored research, less is known about sex disparities in the broader landscape of modern oncologic randomized controlled trials. Using ClinicalTrials.gov, we identified randomized controlled trials related to colorectal or lung cancer (the two most common non-sex-specific disease sites). Among the 147 included trials, the proportion of female patients enrolled on trial was on average 6.8% (95% confidence interval = −8.8% to –4.9%) less than the proportion of female patients in the population by disease site ( P  < .001). Whereas no statistically significant underrepresentation of women was noted within the 26 cooperative group trials, sex disparities were markedly heightened for the 121 noncooperative-group-sponsored trials. Furthermore, underrepresentation of women did not improve with time. Future efforts should therefore focus on addressing these pervasive sex-based enrollment disparities beyond cooperative group trials alone.